(3caGjI GdCQjH aj eTGhQI GdWHjHs - (3SQj GdOjf CMeO Hf eMeO GdYdaj, GdTgjQ HGHf GdUGFZ,J (B991 (3g` s ((3eMji GdOjf eMeO , NGOe GdLGhdjI s)
(3ChdgG (B:s
(3jGef Mce Sjha GdYOe aj fMhQ GdehLhOGJ hMce , hbOe Hg bOe bOQg hbOQJg aj GdbOe , NOeJ Hg NRGFfg GdYGdjI (B((3TjN GdGSdGe CHj GdTaGA MSf(B) s
(3BNQgG (B:s
(3hdjcf gPG BNQ eG jQGOg ef GdcdGe aj gPG GdebGe s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdQGHYs
(3fSNI KGfjIs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfj (B- (3U (B207 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdWHs